KEANEKARAGAMAN FAMILIA POACEAE DI KAWASAN RAWA DESA SUNGAI LUMBAH, KABUPATEN BARITO KUALA - Riza Arisandi; Mochamad Arief Soendjoto; Dharmono Dharmono (Universitas Lambung Mangkurat, 2019)
Grass can be said to be one of the most successful land plants and is found in all types of growing sites and a variety of circumstances. The Poaceae family is the fourth largest family of flowering plants in the world and there are around 11,000 species with 800 genera. A large diversity of species characterizes a stable community. The term swamp is generally closely related to the conditions of standing water, tidal overflows, floods, and mud. This study aims to identify and find out the diversity index (H') of the Poaceae family in the swamp area of Sungai Lumbah village, Barito Kuala district. The steps of this research are determining the location of the study, observing and identifying species, counting the number of clumps per species at each sample point, tabulating data to obtain the diversity index (H '), measuring environmental parameters. Based on observations, 14 species of the Poaceae family were found, namely Bambusa sp., Brachiaria mutica, Digitaria longiflora, Eleusine indica, Eragrostis unioloides, Imperata cylindrica, Ischaemum muticum, Oryza sativa, Panicum paludosum, Panicum repens, Paspalum commersonii, Paspalum conjugatum, Phragmites vallatoria, and Saccharum officinarum. The Poaceae family diversity index in the swampy area of Sungai Lumbah village is moderate (H' = 2.49).